An asymptotic result for linear nonhomogeneous mixed type differential equation - Ali Fuat Yeniçerioğlu (E-Journal of Analysis and Applied Mathematics)
We consider a nonhomogeneous linear mixed type differential equation with variable coefficients and establish an asymptotic result for its solutions. Our result is obtained by the use of a solution of the so-called generalized characteristic equation of the corresponding homogeneous linear mixed type differential equation.